Atorvastatin, but not pravastatin, inhibits cardiac Akt/mTOR signaling and disturbs mitochondrial ultrastructure in cardiac myocytes. Issue 1 (31st August 2018) - Godoy, Joseph C.; Niesman, Ingrid R.; Busija, Anna R.; Kassan, Adam; Schilling, Jan M.; Schwarz, Anna; Alvarez, Erika A.; Dalton, Nancy D.; Drummond, John C.; Roth, David M.; Kararigas, Georgios; Patel, Hemal H.; et al.
ABSTRACT: Statins, which reduce LDL‐cholesterol by inhibition of 3‐hydroxy‐3‐methylglutaryl–coenzyme A reductase, are among the most widely prescribed drugs. Skeletal myopathy is a known statin‐induced adverse effect associated with mitochondrial changes. We hypothesized that similar effects would occur in cardiac myocytes in a lipophilicity‐dependent manner between 2 common statins: atorvastatin (lipophilic) and pravastatin (hydrophilic). Neonatal cardiac ventricular myocytes were treated with atorvastatin and pravastatin for 48 h. Both statins induced endoplasmic reticular (ER) stress, but only atorvastatin inhibited ERK1/2 T202/Y204, Akt Ser473, and mammalian target of rapamycin signaling; reduced protein abundance of caveolin‐1, dystrophin, epidermal growth factor receptor, and insulin receptor‐β; decreased Ras homolog gene family member A activation; and induced apoptosis. In cardiomyocyte‐equivalent HL‐1 cells, atorvastatin, but not pravastatin, reduced mitochondrial oxygen consumption. When male mice underwent atorvastatin and pravastatin administration per os for up to 7 mo, only long‐term atorvastatin, but not pravastatin, induced elevated serum creatine kinase; swollen, misaligned, size‐variable, and disconnected cardiac mitochondria; alteration of ER structure; repression of mitochondria‐ and endoplasmic reticulum–related genes; and a 21% increase in mortality in cardiac‐specific vinculin‐knockout mice during the first 2 months of administration. To our knowledge, we are the first to demonstrate in vivo that long‐term atorvastatin administration alters cardiac ultrastructure, a finding with important clinical implications.——Godoy, J. C., Niesman, I. R., Busija, A.R., Kassan, A., Schilling, J. M., Schwarz, A., Alvarez, E. A., Dalton, N. D., Drummond, J. C., Roth, D.M., Kararigas, G., Patel, H. H., Zemljic‐Harpf, A. E. Atorvastatin, but not pravastatin, inhibits cardiac Akt/mTOR signaling and disturbs mitochondrial ultrastructure in cardiac myocytes. FASEB J. 33, 1209–1225 (2019). www.fasebj.org